Effectiveness of Agricultural Information Disseminated through Social Media - Sandeep, Guntukogula Pattabhi; Prashanth, Pasunoori; Sreenivasulu, Middhe; Madavilata, Anne (Indian Journal of Extension Education, 2022)
The study conducted to understand the effectiveness of agricultural information disseminated through social media as perceived by the farmers in three erstwhile districts of the Southern Telangana zone of Telangana state, with a sample size of 120 in year 2020. Effectiveness of Agricultural Information Index (EAII) was developed for the study by selecting eight indicators. It was found that (39.17%) of the respondents perceived effectiveness of agriculture information disseminated through social media as a medium level. Age and farming experience were found to be negative and significant with the effectiveness of agricultural information perceived by respondents. Digital literacy, farm size, social media network, social media usage, mode of access and preference, readiness to accept information, social media participation was positive and significant in relation to perceived effectiveness, and the variable information processing was found non-significant. The results shown that more than half of the respondents perceived information received on social media is effective. Social media platforms can be utilised effectively by developing better interface and information content to pictures and video format.